Residential renovations: Understanding cost-disruption trade-offs - John A. Curtis; Gianluca Grilli; Muireann Lynch (The Economic and Social Research Institute (ESRI), 2024)
Disruption and mess associated with energy efficiency retrofits is one aspect that is rarely considered in studies investigating households' preferences for energy renovations. Using a choice experiment, we estimate a price for residential retrofit disruption, finding it represents a substantial proportion of associated energy cost savings among some households. There is considerable variance in willingness to pay for both energy cost savings and disruption avoidance, consistent with experience of many households investing in energy retrofits but also of government retrofit schemes falling far short of policy targets. Just 1-in-4 households are actively receptive to retrofit policy supports, and disruption posing a significant barrier to undertaking energy retrofits, means both contribute to the slow progress against public policy targets to improve residential energy efficiency.
Keywords: 330; Disruption; Barrier; Retrofit; Energy efficiency